Can Agroforestry Contribute to Food and Livelihood Security for Indonesia’s Smallholders in the Climate Change Era? - Sudomo, A.; Leksono, B.; Tata, H.L.; Rahayu, A.A.D.; Umroni, A.; Rianawati, H.; Asmaliyah; Krisnawati; Setyayudi, A.; Utomo, M.M.B.; Pieter, L.A.G.; Wresta, A.; et al. (MDPI, 2023)
In Indonesia, smallholders have historically practiced agroforestry, which warrants examination in terms of food and livelihood security within sustainable community forest frameworks. Based on a literature review, we analyzed these two forms of security related to smallholder agroforestry practices. Findings indicate diverse agroforestry systems, with 88% focusing on non-timber forest products (NTFPs) and 12% on timber. While 42% prioritize direct food supply, 58% emphasize income generation through product sales. However, agroforestry that does not produce food for direct consumption by smallholders generates revenue for purchasing food necessities. Agroforestry supports both food needs (46–61%) and income (51–54%) for smallholders, surpassing traditional agriculture (13%). Semi-commercial agroforestry (57%) is a predominant livelihood prospect. The remaining 27% are purely subsistence, and 15% are purely commercial. However, the commercialization of agroforestry that focuses only on high-value commodities results in a negative impact on biodiversity. There is a concomitant decrease in environmental services for climate change mitigation and adaptation. Biodiversity remains crucial for climate resilience, health care, and food security in rural communities. Semi-commercial agroforestry is a midpoint for achieving multifunctional agriculture (biodiversity, soil and water conservation, food security, and income) in the climate change era. The research directly related to food security and ecosystem services quantification remains limited, necessitating further investigation. Policy support and incentives are essential for smallholders practicing complex agroforestry for climate adaptation and mitigation.